Fam83h null mice support a neomorphic mechanism for human ADHCAI. Issue 1 (21st September 2015) - Wang, Shih‐Kai; Hu, Yuanyuan; Yang, Jie; Smith, Charles E.; Richardson, Amelia S; Yamakoshi, Yasuo; Lee, Yuan‐Ling; Seymen, Figen; Koruyucu, Mine; Gencay, Koray; Lee, Moses; Choi, Murim; et al.
Abstract: Truncation mutations in FAM83H (family with sequence similarity 83, member H) cause autosomal dominant hypocalcified amelogenesis imperfecta (ADHCAI), but little is known about FAM83H function and the pathogenesis of ADHCAI. We recruited three ADHCAI families and identified two novel (p.Gln457*; p.Lys639*) and one previously documented (p.Q452*) disease‐causing FAM83H mutations. We generated and characterized Fam83h ‐knockout/ lac Z‐knockin mice. Surprisingly, enamel thickness, density, Knoop hardness, morphology, and prism patterns were similar in Fam83h +/+, Fam83h +/−, and Fam83h −/− mice. The histology of ameloblasts in all stages of development, in both molars and incisors, was virtually identical in all three genotypes and showed no signs of pathology, although the Fam83h −/− mice usually died after 2 weeks and rarely survived to 7 weeks. LacZ expression in the knockin mice was used to report Fam83h expression in the epithelial tissues of many organs, notably in skin and hair follicles, which manifested a disease phenotype. Pull‐down studies determined that FAM83H dimerizes through its N‐terminal phospholipase D‐like (PLD‐like) domain and identified potential FAM83H interacting proteins. Casein kinase 1 (CK1) interacts with the FAM83H PLD‐like domain via an F 270 ‐X‐X‐X‐F 274 ‐X‐X‐X‐F 278 motif. CK1 can phosphorylate FAM83H in vitro, and many phosphorylation sites were identified in the FAM83H C‐terminus. Truncation of FAM83H alters its subcellular localization and that of CK1. Our results support the conclusion that FAM83H is not necessary for proper dental enamel formation in mice, but may act as a scaffold protein that localizes CK1. ADHCAI is likely caused by gain‐of‐function effects mediated by truncated FAM83H, which potentially mislocalizes CK1 as part of its pathological mechanism. Abstract : We identified three FAM83H mutations (two novel ones) that cause autosomal dominant hypocalcified amelogenesis imperfecta (ADHCAI). We generated and characterized Fam83h ‐knockout/ NLS‐lacZ ‐knocking mice, characterized FAM83H self‐interactions and interactions with casein kinase 1, and conclude that FAM83H truncation mutations cause ADHCAI through a gain‐of‐function mechanism.